Federalism and Public Health Governance. The Role of State-Level Horizontal Coordination During Responses to Covid-19 in Brazil (Desarrollo Económico. Revista de Ciencias Sociales, 2024)
The paper chronicles the Covid-19 pandemic as a defining moment, which works to propel a cascade of institutional responses – uncoordinated at first, but that reach an equilibrium later in time for establishing a multi-level governance (MLG) based on horizontal coordination among subnational units over specific issue-areas. This moment affords a special opportunity to observe the confrontation between the federal government and subnational units in Brazil over the nature of the response and the prerogative to act. Of special interest to our understanding of the impact of Covid-19 in Brazil are two related questions. First, can we speak of the “national” policy responses to the pandemic as a definite departure from the pattern of interaction that characterizes Brazilian democratic federalism? Secondly, if so, which are the implications of this transformative process in terms of public health governance? More specifically, how the relevant changes in the political dynamics of Brazilian federalism affect the provision of public health goods - and the prospects of democratic governance? Our analysis concludes that by putting the pattern of cooperation between the federal government and subnational entities under strain, Bolsonaro’s attempt to resume presidential prerogatives prompted the improvement in inter-governmental relations (IGR) of Brazilian states at the horizontal level and, consequently, of MLG per policy domain. This shift is a key aspect of what can be broadly described as the realignment of the political and social forces engaged in responding to the global challenge of public health governance within the framework of the 1988 Constitution.
Keywords: Federalismo, Gobernanza multinivel, Federalismo brasileño, Covid-19.